PENGARUH NET LABA MARGIN DAN EARNING PER SAHAM TERHADAP HARGA SAHAM PADA PT. MANDALA MULTIFINANCE, Tbk - sartika, andi; Ifwana, Ifwana (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to examine the influence of Net Profit Margin (NPM) and Earnings Per Share (EPS) on stock prices at PT Mandala Multifinance, Tbk. The types of data used in this research are both qualitative and quantitative, with secondary data serving as the primary data source. The analytical methods employed include multiple linear regression, coefficient of determination (R²), correlation coefficient (R), as well as F-test and t-test. The results show the regression equation as follows: Y = 821.104 + 18.682X₁ + 0.680X₂ + e. The coefficient of determination (R²) is 0.043, and the correlation coefficient (R) is 0.208, indicating a very weak relationship between the independent variables and the stock price. The F-test result shows that the calculated F-value (0.14) is less than the critical F-value (5.14), indicating that NPM and EPS simultaneously have no significant effect on stock prices. Partially, the t-test results show that NPM (t-value = 0.32) and EPS (t-value = 0.12) are both lower than the critical t-value (1.943), suggesting that neither variable has a significant influence on the stock price of PT Mandala Multifinance, Tbk.